1999
DOI: 10.1002/jlb.66.1.113
|View full text |Cite
|
Sign up to set email alerts
|

Differential iron transport into phagosomes isolated from the RAW264.7 macrophage cell lines transfected with Nramp1Gly169 or Nramp1Asp169

Abstract: The transport of iron by RAW264.7 macrophage cell lines transfected with either Nramp1 Gly169 (resistant) or Nramp1 Asp169 (susceptible) alleles was assessed. We found no difference between resistant and susceptible cells in the rate of Fe import or export when Fe transport was measured in intact cells. In contrast, the rate of Fe import by latex-bead phagosomes isolated from resistant cells was more than double the rate by latex-bead phagosomes from susceptible cells. Similarly, phagosomes isolated from resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
104
2

Year Published

2000
2000
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(117 citation statements)
references
References 27 publications
(43 reference statements)
10
104
2
Order By: Relevance
“…They compared phagosomes isolated from macrophages stably expressing wild type Slc11a1 Gly 469 versus mutant/functionally null Slc11a1 Asp 469 , and observed greater import of iron into phagosomes from wild type macrophages. They also found that phagosomes isolated from wild type cells pre-labeled with 55 Fe-citrate before phagocytosis contained up to four times more iron compared with phagosomes from mutant cells, and that treatment of wild type macrophages with the lysomotrophic agents chloroquine or ammonium chloride reduced the import of iron significantly (23,24). Multiple groups have compared intracellular iron levels and determined that mutant macrophages have higher cytoplasmic iron than wild type macrophages (6,54,55,57,58).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They compared phagosomes isolated from macrophages stably expressing wild type Slc11a1 Gly 469 versus mutant/functionally null Slc11a1 Asp 469 , and observed greater import of iron into phagosomes from wild type macrophages. They also found that phagosomes isolated from wild type cells pre-labeled with 55 Fe-citrate before phagocytosis contained up to four times more iron compared with phagosomes from mutant cells, and that treatment of wild type macrophages with the lysomotrophic agents chloroquine or ammonium chloride reduced the import of iron significantly (23,24). Multiple groups have compared intracellular iron levels and determined that mutant macrophages have higher cytoplasmic iron than wild type macrophages (6,54,55,57,58).…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, they suggest that Slc11a1 could starve intracellular pathogens of essential cations, thereby mediating resistance to infection. Contrary to this were the studies of Kuhn et al (23,24) that demonstrated differential transport of iron into Mycobacterium-containing phagosomes isolated from the RAW264.7 macrophage cell lines transfected with wild type Slc11a1 Gly 169 or mutant Slc11a1 Asp 169 , and into phagosomes of intact infected macrophages. The view of these authors was that delivery of ferrous iron into the phagolysosome of infected macrophages could contribute to antimicrobial activity through production of toxic radical via the Haber-Weiss and Fenton reactions.…”
mentioning
confidence: 81%
“…In addition, we have observed that an Nramp1 mutant with altered trafficking properties is expressed at the plasma membrane of Chinese hamster ovary cells, where it mediates cellular uptake of not only 54 Mn 2ϩ but also 55 Fe 2ϩ (J. R. Forbes and P.G., unpublished data). These and studies by Khun et al (24,25) suggest that Nramp1 may also transport iron at the phagosomal membrane. Therefore, we tested the effect of two iron chelators, DFO and SIH, on the maturation of SCVs.…”
Section: Results Inmentioning
confidence: 70%
“…These authors conclude that Nramp1 may transport metals from the cytoplasm into the phagosome by a proton antiporter mechanism (26). It has been proposed that increased phagosomal iron may stimulate oxygen radical formation in situ via the Haber-Weiss reaction (24)(25)(26). On the other hand, we have used a metal-sensitive and pH-resistant fluorescent dye (Fura-FF6) chemically coupled to zymosan particles to monitor by microfluorescence imaging the effect of Nramp1 on divalent cation fluxes across the membrane of phagosomes formed in live primary macrophages (27).…”
mentioning
confidence: 97%
See 1 more Smart Citation